PENGARUH MEDIA SOSIAL TERHADAP KETERLIBATAN PENGGEMAR DALAM OLAHRAGA PROFESIONAL - Dindin Abidin (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
The rise of social media has transformed how fans engage with professional sports, creating a more dynamic and interactive experience. This study aims to analyze the impact of social media on fan engagement in professional sports, focusing on emotional, behavioral, and cognitive aspects. A quantitative approach was employed, using surveys distributed to sports fans actively engaged on various social media platforms. The collected data were analyzed using statistical techniques to determine the relationship between social media usage intensity and fan engagement levels. The findings indicate that social media significantly enhances fan engagement by providing direct access to information, facilitating online discussions, and enabling interactions with athletes and sports teams. Factors such as usage frequency, content type, and direct engagement with teams or athletes contribute to increased fan loyalty and enthusiasm. This study offers valuable insights for sports organizations, marketers, and social media managers to optimize digital strategies for strengthening fan engagement.